The next global stage : challenges and opportunities in our borderless world - d (Upper Saddle River, NJ : Wharton School Pub., 2007)
"Ohmae shows why yesterday's economic theories are collapsing, and illuminates a new world driven by 'region states' and new economic platforms, not traditional nations or traditional economics ... Ohmae [also] shows what it'll take to succeed there, as a company, a nation, and as an individual."--Page 4 of cover
Includes index.
Keywords: Nation-state and globalization; Culture and globalization; International economic integration